A Design of a Small-Aperture Low-Profile Omnidirectional Conformal Antenna - Jieying Bai; Xi Li; Ziyu Zhang; Junjun Wu; Lin Yang (Micromachines)
In this article, a small-aperture, low-profile, and omnidirectional conformal antenna is proposed which can be utilized on space-limited equipment platforms such as airplanes, ships, and vehicles. The antenna consists of an open metal cavity, a discone antenna, a parasitic structure, and a radome. The small aperture and low-profile design of the metal cavity result in a rapid narrowing of the bandwidth of the discone antenna. Therefore, we introduce a parasitic structure that not only enlarges the impedance bandwidth by adding a resonant point, but can also be used to adjust the unroundness of the horizontal pattern. Meanwhile, the conformal design of the antenna with four surfaces of different curvatures is presented. The simulation and testing results demonstrate that the antenna can achieve a VSWR of less than 2 within a bandwidth of 1.95–2.62 GHz (29.3%), with a minimum aperture of 0.43 omnidirectional radiation pattern, with a gain exceeding −2.2 dBi in the azimuthal plane. This antenna offers the advantages of a small aperture, low profile, and conformal capability. Furthermore, the resonances of high and low frequencies can be adjusted through two different structures, enhancing the flexibility of antenna design.